See it now confronts McCarthyism : television documentary and the politics of representation - Rosteck, Thomas, 1951- (Studies in rhetoric and communication., 1994)
In late 1953 and early 1954, Edward R. Murrow and Fred W. Friendly's See It Now television documentary broadcast a series of four programs that dealt with abuses of McCarthyism: "The Case of Milo Radulovich," "An Argument in Indianapolis," "A Report on Senator McCarthy," and "Annie Lee Moss Before the McCarthy Committee." Each program focused upon elements of McCarthyism - the blacklist, the suspicion of anything "liberal," the Congressional hearing and immunity, even the political tactics of Senator Joseph R. McCarthy himself. These justifiably acclaimed telecasts have been credited with forever defining the form of television documentary and with greatly contributing to the "downfall" of the senator and the movement that took his name. Rosteck studies these programs for what they reveal about the rhetoric of television documentary and the ideological representations within. He considers the four programs as artifacts that expose a crucial era in American political life and represent cultural and ideological struggles. Specifically, Rosteck analyzes the programs as instances of public discourse that symbolically reframe McCarthyism, and he provides us with the first sustained exploration and case study of documentary television as a discrete genre. He explores how the programs "work" as public argument in a way that goes beyond an analysis of content or propositional "logic." Indeed it may be, Rosteck says, that See It Now uses the form of the documentary medium and the myth it fosters - that of the open and free exchange of ideas - as "argument" against McCarthyism. Because he sets the programs in their particular situation and historical context, Rosteck also helps us understand a unique era in recent American history what one historian has called "The Decade of Fear" when the national mood was one of mistrust and suspicion. The See It Now programs influenced the development of both the television documentary and the television industry. Rosteck identifies the birth of the documentary form in these famous programs and shows how the content and structure of the programs reflect certain social and cultural assumptions. As cultural exploration, this volume not only shows a history of the era of the programs; it also illuminates a short segment of recent American experience through documentary artifacts from the time